T-Bet Controls Susceptibility of Mice to Coxiella burnetii Infection - Mezouar, Soraya; Lepidi, Hubert; Omar Osman, Ikram; Gorvel, Jean-Pierre; Raoult, Didier; Mege, Jean-Louis; Bechah, Yassina (Frontiers in Microbiology, 2020)
T-bet is a transcription factor known to initiate and coordinate the gene expression program during Th1 differentiation, which is crucial for clearance of intracellular pathogens. Q fever is a worldwide zoonosis caused by Coxiella burnetii. This bacterium is transmitted to humans by aerosol. Indeed, the inhibition of the Coxiella-specific adaptive Th1 immune response leads to persistent infection and organ injury. How deficiency of T-bet affects host infection by C. burnetii has not been investigated. Here, using mice with a deletion of the T-bet gene and an airborne mode of infection to reproduce the natural conditions of C. burnetii infection, we showed that infected T-bet-/- mice were more affected than wild type mice. The lack of T-bet leads to a defective bacterial control, intense replication, persistent infection and organ injury manifesting as an increased number of granulomas. The absence of T-bet was also associated with an impaired immune response. Indeed, the production of the immunomodulatory cytokines interleukin (IL)-6 and IL-10 was increased whereas the expression of microbicidal genes by splenocytes was impaired. Moreover, the absence of T-bet exhibited impaired production of interferon-γ, the principal cytokine released by Th1 effector cells. Thus, our study highlights the key role of T-bet in the control of C. burnetii infection in mice and leads to a reappraisal of granulomas in the pathogenesis of Q fever disease.